Development of a bench-top extra-cleanroom for DNA amplification. (July 2016) - Takahashi, Hirokazu; Satoh, Takahiro; Kanahara, Hiroko; Kubota, Yuji; Hirose, Tamaki; Yamazaki, Hiroyuki; Yamamoto, Kimiko; Okamura, Yoshiko; Suzuki, Taketo; Kobori, Toshiro
Prevention of airborne contamination has become an important factor in biotechnology; however, conventional laminar-airflow cabinets (LAF-cabinets) are no longer sufficient as a countermeasure against nano-sized airborne contaminants in the laboratory. Here we present a bench-top extra-cleanroom classified as ISO-1 that can prevent contamination from airborne nanoparticles. This bench-top extra-cleanroom consists of a novel clean-zone-creating system that is equipped with nanofibrous, nonwoven filters. In addition, the cleanroom is also equipped with an ionizer to prevent plasticware from collecting dust by electrostatic charge attraction. This combination of features allows the cleanroom to prevent DNA contamination derived from airborne nanoparticles. Our extra-cleanroom with ionizer could be useful in various areas of biotechnology that are easily affected by airborne contaminants.